2020
DOI: 10.1111/jnc.15041
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemistry of the Kölliker‐Fuse nucleus from a respiratory perspective

Abstract: The Kölliker‐Fuse nucleus (KF) is a functionally distinct component of the parabrachial complex, located in the dorsolateral pons of mammals. The KF has a major role in respiration and upper airway control. A comprehensive understanding of the KF and its contributions to respiratory function and dysfunction requires an appreciation for its neurochemical characteristics. The goal of this review is to summarize the diverse neurochemical composition of the KF, focusing on the neurotransmitters, neuromodulators, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 281 publications
(461 reference statements)
1
21
0
Order By: Relevance
“…A relatively immature respiratory control system could also explain the increased prevalence of apneas after MM. Lastly, the effects of opioids on other aspects of the respiratory control network could also contribute to these deficits in breathing, including regions influencing pattern and rate (e.g., Kölliker-Fuse, locus coeruleus, and post-inspiratory complex) ( Anderson et al, 2016b ; Kliewer et al, 2019 ; Saunders and Levitt, 2020 ; Varga et al, 2020a , b ). Future studies should focus on identifying the mechanisms of these breathing deficits and involvement of different aspects of the respiratory control circuitry.…”
Section: Discussionmentioning
confidence: 99%
“…A relatively immature respiratory control system could also explain the increased prevalence of apneas after MM. Lastly, the effects of opioids on other aspects of the respiratory control network could also contribute to these deficits in breathing, including regions influencing pattern and rate (e.g., Kölliker-Fuse, locus coeruleus, and post-inspiratory complex) ( Anderson et al, 2016b ; Kliewer et al, 2019 ; Saunders and Levitt, 2020 ; Varga et al, 2020a , b ). Future studies should focus on identifying the mechanisms of these breathing deficits and involvement of different aspects of the respiratory control circuitry.…”
Section: Discussionmentioning
confidence: 99%
“…While both agonists have similar potency and binding affinity to OX2R ( Sakurai et al, 1998 ; Irukayama-Tomobe et al, 2017 ), the OXR-B peptide is less selective and may also bind to OX1R ( Sakurai et al, 1998 ; Kilduff and Peyron, 2000 ), which may explain the more substantial changes in respiratory pattern following peptide injections. OX1R expression has been described in the KF and parabrachial region in rodents ( Marcus et al, 2001 ; Varga et al, 2020 ), and the KF in humans ( Lavezzi et al, 2016 ). Histological examination of the KF of infants who died of sudden infant death syndrome (SIDS) showed significantly reduced levels of OX1R expression compared to non-SIDS cases ( Lavezzi et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Yan et al 2021 previously found that BNST-PBN neurons in a mouse model of Dravet Syndrome and SUDEP were less likely to fire action potentials in response to current injections, building evidence on the potential importance of this pathway and risk for SUDEP. In Sudden Infant Death Syndrome (SIDS), another cause of sudden death due to respiratory dysfunction, and in Rett Syndrome, a neurodevelopmental disorder with significant apneas, the Köllliker-Fuse/lateral PBN have also been implicated (Abdala et al 2016;Varga et al 2020;Lavezzi et al 2019). More broadly, stimulation of BNST-PBN projection neurons has also been shown to decrease respiratory rate (Kim et al, 2013).…”
Section: Discussionmentioning
confidence: 99%